Inducible In Vivo Silencing of Brd4 Identifies Potential Toxicities of Sustained BET Protein Inhibition - Jessica E. Bolden; Nilgun Tasdemir; Lukas E. Dow; Johan H. van Es; John E. Wilkinson; Zhen Zhao; Hans Clevers; Scott W. Lowe (Cell Reports, 2014)
BET family proteins are novel therapeutic targets for cancer and inflammation and represent the first chromatin readers against which small-molecule inhibitors have been developed. First-generation BET inhibitors have shown therapeutic efficacy in preclinical models, but the consequences of sustained BET protein inhibition in normal tissues remain poorly characterized. Using an inducible and reversible transgenic RNAi mouse model, we show that strong suppression of the BET protein Brd4 in adult animals has dramatic effects in multiple tissues. Brd4-depleted mice display reversible epidermal hyperplasia, alopecia, and decreased cellular diversity and stem cell depletion in the small intestine. Furthermore, Brd4-suppressed intestines are sensitive to organ stress and show impaired regeneration following irradiation, suggesting that concurrent Brd4 suppression and certain cytotoxic therapies may induce undesirable synergistic effects. These findings provide important insight into Brd4 function in normal tissues and, importantly, predict several potential outcomes associated with potent and sustained BET protein inhibition.